A review of e-portfolios in Malaysian Higher Education - Wirawati Ngui Yi Xe; Vincent Pang; Wendy Hiew (Human Resource Management Academic Research Society, 2019)
Technology has enhanced methods and resources to teach and assess learners. An example is the e-Portfolio, a tool that has the ability to accommodate a plethora of digital learning evidences. Due to its digital nature, the e-Portfolio also enables easy access to a wide range of stakeholders. Thus, e-Portfolios have gradually replaced paper-based portfolios as a more relevant educational tool. This trend is also evident in Malaysia whereby academicians and researchers have explored the use of e-Portfolio in higher learning institutions. A review is therefore timely to provide an overview of the present state of knowledge. This study aims to present a review of empirical research involving e-Portfolios in the Malaysian higher education context. As such, the review takes into account a range of studies involving various stakeholders, programmes, and higher learning institutions. The study provides a comprehensive overview of the e-Portfolio studies that have been conducted thus far and reveals the contributions of e- Portfolio as an educational tool in Malaysia.